Assessing the Impact of Service Quality, Price, and Perceived Value on Customer Satisfaction: A Case Study of Jabodebek LRT at Jatimulya Station - Saputra, Joshua Galatia (APPS Publications, 2024)
The objective of this research is to investigate the influence of service quality, price, and perceived value on customer satisfaction among users of the Jabodebek LRT at Jatimulya Station. Given the increasing usage of the Jabodebek LRT and the reported dissatisfaction among customers regarding service quality, particularly at Jatimulya Station, the study aims to identify the key factors that contribute to customer satisfaction. The research employed a quantitative methodology with a comparative causality approach, focusing on the influence of service quality, price, and perceived value on customer satisfaction among users of the Jabodebek LRT at Jatimulya Station, utilizing a questionnaire distributed via Google Forms. Data analysis was conducted using the Partial Least Square (PLS) method with SmartPLS software to assess the relationships between the variables and ensure the validity and reliability of the measurement models. The findings of the research indicate that all three variables—service quality, price, and perceived value—significantly influence customer satisfaction among users of the Jabodebek LRT at Jatimulya Station. The novelty of the research lies in its focus on the specific context of the Jabodebek LRT at Jatimulya Station, addressing the unique challenges and customer feedback related to service quality, pricing, and perceived value. This study is among the first to systematically analyze these factors and their direct impact on customer satisfaction in this newly operational mass transit system, providing valuable insights for future improvements.